Biomass-Derived Thermally Annealed Interconnected Sulfur-Doped Graphene as a Shield against Electromagnetic Interference - Shahzad, Faisal; Kumar, Pradip; Kim, Yoon-Hyun; Hong, Soon Man; Koo, Chong Min (American Chemical Society, 2016)
Electrically conductive thin carbon materials have attracted remarkable interest as a shielding material to mitigate the electromagnetic interference (EMI) produced by many telecommunication devices. Herein, we developed a sulfur-doped reduced graphene oxide (SrGO) with high electrical conductivity through using a novel biomass, mushroom-based sulfur compound (lenthionine) via a twostep thermal treatment. The resultant SrGO product exhibited excellent electrical conductivity of 311 S cm(-1), which is 52% larger than 205 S cm(-1) for undoped rGO. SrGO also exhibited an excellent EMI shielding effectiveness of 38.6 dB, which is 61% larger than 24.4 dB measured for undoped rGO. Analytical examinations indicate that a sulfur content of 1.95 atom % acts as n-type dopant, increasing electrical conductivity and, therefore, EMI shielding of doped graphene.
Keywords: OXYGEN REDUCTION REACTION; METAL-FREE ELECTROCATALYSTS; ELECTRICAL-PROPERTIES; MICROWAVE-ABSORPTION; CHEMICAL-REDUCTION; GRAPHITE OXIDE; COMPOSITES; PERFORMANCE; LIGHTWEIGHT; FACILE